Risk Factors of Anterior Circulation Intracranial Aneurysm Rupture: Extracranial Carotid Artery Tortuosity and Aneurysm Morphologic Parameters - Pei, Yusong; Xu, Zhihua; Liang, Guobiao; Jin, Hai; Duan, Yang; Yang, Benqiang; Qiao, Xinxin; You, Hongrui; Xing, Dengxiang (Frontiers in Neurology, 2021)
Background: To explore the risk factors of anterior circulation intracranial aneurysm rupture based on extracranial carotid artery (ECA) tortuosity. Methods: This retrospective study, conducted from January 1, 2017, to March 1, 2021, collected and reviewed the clinical and imaging data of 308 patients with anterior circulation intracranial aneurysm (133 [43.2%] patients in the ruptured aneurysm group; 175 [56.8%] patients in the unruptured aneurysm group). Computed tomography angiography (CTA) of the head and neck was used to determine the ECA tortuosity (normal, simple tortuosity, kink, coil) and the morphologic parameters of the aneurysms. The relationship of aneurysm rupture to ECA tortuosity and the morphologic parameters was analyzed. Results: After univariate analysis, kink, angle of flow inflow (FA), aspect ratio (AR), aneurysm length (L), the distance from the tortuosity to the aneurysm (Distance), and size ratio (SR) were significantly correlated with anterior circulation intracranial aneurysm rupture (P < 0.05). Spearman correlation analysis showed that ECA tortuosity was correlated with FA and SR (P < 0.05). Multiple logistic analyses showed that FA (odds ratio [OR], 1.013; 95% CI, 1.002-1.025), SR (OR, 1.521; 95% CI, 1.054-2.195), and kink (OR, 1.823; 95% CI, 1.074-3.096) were independently associated with aneurysm rupture. Conclusion: Study results suggest that FA, SR, and ECA kink were independent risk factors associated with anterior circulation intracranial aneurysm rupture.